2016
DOI: 10.1002/admi.201600253
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Solution‐Processed Two‐Component Bilayer Phthalocyaninato Copper‐Based Heterojunctions with Interesting Ambipolar Organic Transiting and Ethanol‐Sensing Properties

Abstract: International audienceThe two-component phthalocyaninato copper-based heterojunctions fabricated from n-type CuPc(COOC8H17)(8) and p-type CuPc(OC8H17)(8) by a facile two-step solution-processing quasi-Langmuir-Shafer method with both n/p- and p/n-bilayer structures are revealed to exhibit typical ambipolar air-stable organic thin-film transistor (OTFT) performance. The p/n-bilayer devices constructed by depositing CuPc(COOC8H17)(8) film on CuPc(OC8H17)(8) sub-layer show superior OTFT performance with hole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…A static recovery period (full recovery time) varied respectively from 1.6 to 7 min for 1 and 1.7 to 9 min for 2 to ensure the almost complete recovery after the test gas has been released. As can be seen in Figure and , the negative current responses for the aggregates of 1 and 2 were obtained upon exposure to electron‐accepting NO 2 gases, which are consistent with the sensing behavior reported previously for n‐type semiconductors, respectively . The response to NO 2 for the aggregates of both 1 and 2 highly increased with the increased RH value, Figure (A–C) and 8(A–C).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…A static recovery period (full recovery time) varied respectively from 1.6 to 7 min for 1 and 1.7 to 9 min for 2 to ensure the almost complete recovery after the test gas has been released. As can be seen in Figure and , the negative current responses for the aggregates of 1 and 2 were obtained upon exposure to electron‐accepting NO 2 gases, which are consistent with the sensing behavior reported previously for n‐type semiconductors, respectively . The response to NO 2 for the aggregates of both 1 and 2 highly increased with the increased RH value, Figure (A–C) and 8(A–C).…”
Section: Resultssupporting
confidence: 87%
“…The higher conductivity of 2 with respect to that of 1 might be attributed to the higher ordered molecular arrangement due to the stronger π‐π interactions among the adjacent molecules in the aggregate of 2 as revealed by the UV‐vis, IR spectra and SEM experiments. A similar trend in conducting performance has previously been observed for porphyrins, phthalocyanines and amphiphilic perylene diimides . This result again revealed that the effect of metal center of in‐plane cobalt(II) porphyrin on the tuning of the intermolecular stacking, which then impacts on the electrical conductivity of the materials.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…

years, many efforts have been made toward tuning structural and electronic properties of metal oxides to reduce the working temperature and enhancing gas sensor performance. [17][18][19][20] But most of these cases, metal oxide sensors have to be operated at high temperature or under UV irradiation conditions because of their large bandgap. MOS gas sensors based chemiresistive sensors have ability to measure and monitor trace level concentration of hazardous gases such as NO x , CO x , NH 3 , CH 4 , H 2 S, and SO 2 .

…”
mentioning
confidence: 99%